Effect of colloidal particle size on physicochemical properties and aggregation behaviors of two alkaline soils - Y. Yan; X. Zhang; C. Xu; C. Xu; J. Liu; F. Hu; F. Hu; Z. Geng; Z. Geng (SOIL)
Colloidal particles are the most active soil components, and they vary in elemental composition and environmental behaviors with the particle size due to the heterogeneous nature of natural soils. The purposes of the present study are to clarify how particle size affects the physicochemical properties and aggregation kinetics of soil colloids and to further reveal the underlying mechanisms. Soil colloidal fractions, from two alkaline soils – Anthrosol and Calcisol – were subdivided into three ranges: d<2 µm, d<1 µm and d<100 nm. The organic and inorganic carbon contents, clay mineralogy and surface electrochemical properties, including surface functional groups and zeta potentials, were characterized. Through a time-resolved light scattering technique, the aggregation kinetics of soil colloidal fractions were investigated, and their critical coagulation concentrations (CCCs) were determined. With decreasing colloidal particle diameter, the total carbon content, organic carbon, organic functional groups' content and illite content all increased. The zeta potential became less negative, and the charge variability decreased with decreasing particle diameter. The CCC values of Anthrosol and Calcisol colloids followed the descending order of d<100 nm, d<1 µm and d<2 µm. Compared with the course factions (d<1 and d<2 µm), soil nanoparticles were more abundant in organic carbon and more stable clay minerals (d<100 nm); thus they exhibited strongest colloidal suspension stability. The differences in organic matter contents and clay mineralogy are the fundamental reasons for the differences in colloidal suspension stability behind the size effects of Anthrosol and Calcisol colloids. The present study revealed the size effects of two alkaline soil colloids on carbon content, clay minerals, surface properties and suspension stability, emphasizing that soil nanoparticles are prone to be more stably dispersed instead of being aggregated. These findings can provide references for in-depth understanding of the environmental behaviors of the heterogeneous soil organic–mineral complexes.